2019
DOI: 10.1007/s00429-019-01965-y
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar neural markers of susceptibility to social isolation and positive affective processing

Abstract: Chronic loneliness predicts mood disturbances and onset of major depressive disorder. However, little research has examined the neural correlates of individual difference in susceptibility to perceiving loneliness. In addition, the role of cerebellum, which is heavily implicated in social, cognitive and affective processes, in loneliness is unclear. We studied 99 healthy individuals divided into susceptible, concordant and robust groups depending on whether the participant’s loneliness level was greater, compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 61 publications
(80 reference statements)
2
23
0
Order By: Relevance
“…Twenty-four studies focused on younger adults (mean age 18–60; [ 24 47 ]), 12 on older adults (mean age >60; [ 48 59 ]), two on adolescents [ 60 , 61 ], and two across the lifespan [ 62 , 63 ]. Most reports included healthy individuals while seven focused on clinical populations: four with depression [ 47 , 49 , 51 , 57 ], and one each with traumatic brain injury (TBI) [ 58 ], schizophrenia [ 28 ], and severe hearing impairment [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-four studies focused on younger adults (mean age 18–60; [ 24 47 ]), 12 on older adults (mean age >60; [ 48 59 ]), two on adolescents [ 60 , 61 ], and two across the lifespan [ 62 , 63 ]. Most reports included healthy individuals while seven focused on clinical populations: four with depression [ 47 , 49 , 51 , 57 ], and one each with traumatic brain injury (TBI) [ 58 ], schizophrenia [ 28 ], and severe hearing impairment [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, higher loneliness scores correlated with reduced GM volumes in the posterior superior temporal sulcus, amygdala, hippocampus/para-hippocampus and cerebellum (Kanai et al ., 2012 ; Düzel et al ., 2019 ); increased GM volumes in the dorsolateral prefrontal cortex (PFC) (Kong et al ., 2015 ); and lower WM density in the bilateral inferior parietal lobule, right insula, posterior temporoparietal junction, posterior superior temporal sulcus, dorsomedial and rostro-lateral PFC (Nakagawa et al ., 2015 ). Moreover, increased GM cerebellar volumes were observed when comparing individuals with v. without susceptibility to loneliness (Wong et al ., 2019 ). Lastly, Stahn et al .…”
mentioning
confidence: 99%
“…Studies investigating the association between loneliness and functional brain correlates analysed the blood oxygenation level-dependant (BOLD) or EEG signals of the samples. Overall, loneliness was associated with different processing of pleasant and unpleasant social stimuli and words with affective value (Cacioppo et al ., 2009 , 2016 ; Inagaki et al ., 2016 ; Wong et al ., 2019 ). Specifically, Cacioppo et al showed that, while viewing pleasant and unpleasant pictures, participants with high v. low perceived loneliness (as measured by the UCLA-LS) had reduced activations of the ventral striatum and the temporoparietal junction and greater activation of the visual cortex (Cacioppo et al ., 2009 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To capture the brain functional activations during tasks, the gradient-echo echo-planar imaging sequence will be used to scan, while the participants are required to complete an Emotional Stroop Task, which may cost approximately 10 min. The task [ 36 ] is a two-run modified emotion-word Stroop. Each run consists of five randomized blocks.…”
Section: Methodsmentioning
confidence: 99%